2019
DOI: 10.1177/0022002719832346
|View full text |Cite
|
Sign up to set email alerts
|

Fighting from the Pulpit: Religious Leaders and Violent Conflict in Israel

Abstract: Religious leaders greatly influence their constituents’ political behavior. Yet, it is unclear what events trigger nationalist attitudes among religious leaders and why this effect occurs more among some religious leaders rather than others. In this article, I examine the content of Israeli Rabbinic rhetoric during different military and political conflicts. Drawing on an original collection of Sabbath pamphlets distributed to Synagogues, I demonstrate that religious rhetoric is highly responsive to levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The religious communication approach has also been turned toward an understanding of the dynamics of other Abrahamic faiths as well, as several studies of the kinds of social and political arguments publicly leveled by rabbis have emerged over the last couple of decades (Djupe & Sokhey, 2003a, 2003b; Freedman, 2019; Sokhey & Djupe, 2006). Work detailing the level of political activity in evidence within synagogues has generally found that they often specialize in offering access to non‐electoral forms of political activity to their adherents, as has been found to be the case with other faith traditions (Kotler‐Berkowitz, 2021).…”
Section: Developmentmentioning
confidence: 99%
“…The religious communication approach has also been turned toward an understanding of the dynamics of other Abrahamic faiths as well, as several studies of the kinds of social and political arguments publicly leveled by rabbis have emerged over the last couple of decades (Djupe & Sokhey, 2003a, 2003b; Freedman, 2019; Sokhey & Djupe, 2006). Work detailing the level of political activity in evidence within synagogues has generally found that they often specialize in offering access to non‐electoral forms of political activity to their adherents, as has been found to be the case with other faith traditions (Kotler‐Berkowitz, 2021).…”
Section: Developmentmentioning
confidence: 99%
“…The crises that emerge in the Middle East are mostly caused by the oil resources possessed by the transcontinental region (Balat, 2006;Peretz, 1963). Several studies (Alashqar, 2018;Canetti et al, 2019;Freedman, 2019;Schiff, 2018) showed that the Israeli-Palestinian conflict is the most intractable issue in these lands around the Mediterranean Sea. Other conflicts related to civil right violation, women's liberation, and education are also emerging (Brown & Bjawi-Levine, 2002;Syed, 2013).…”
mentioning
confidence: 99%